TOILETS TANK! : THEIR INNER WORKINGS - Flynn, Riley; Butzer, Anna; Nuytten, Bobbie (North Mankato, Minnesota : CAPSTONE PRESS, 2018)
"Get ready for some literal bathroom reading. Discover the story behind their home's most under appreciated feature. From facts on how much bodily waste the average person releases a day to information on what the first "toilets" were like. Readers will learn about why we need sanitation and where our waste goes when we flush."--Provided by publisher.
Includes index.
Bibliography : page 31
Keywords: Toilets -- Juvenile literature; Toilets -- History -- Juvenile literature; Sewerage -- Juvenile literature